SURVEY TINGKAT KESEGARAN JASMANI TRC (TIM REAKSI CEPAT) ANGGOTA BPBD KABUPATEN KOLAKA UTARA SULAWESI TENGGARA - Nurasmi Rahim; Ika Sartika; Resky Ana Abadi (Journal Olympic (Physical Education, Health and Sport), 2022)
The level of physical fitness is very influential on a person's creativity and ability to carry out daily activities in the surrounding environment. Components of physical fitness, biomotor components or components of physical condition, are the basic abilities of physical movement or activities of the human body. This physical condition is an indispensable requirement in an effort to improve the movement ability of school-age children and the efficiency of the ability to carry out daily activities. Physical fitness is influenced by many factors, including age, gender, nutrition, exercise and lifestyle of children. This study aims to determine the level of physical fitness of members of the BPBD TRC (Quick Response Team) in North Kolaka Regency, Southeast Sulawesi. This research is included in quantitative descriptive research using survey method with test and measurement techniques. The population used in this study were 15 members of the TRC (Quick Response Team) Kab. Kolaka, Southeast Sulawesi. The results showed that the qualifications for the level of physical fitness of sepaktakraw athletes in Kab. North Kolaka are, as follows: there are 0% (0 TRC Members) in the “very good” category, 13.33% (2 TRC members), in the “good” category, 66.67% (10 TRC members), in the “good” category “medium”, 20% (3 TRC members), in the “less” category, and in the “very poor” category, 0% (0 TRC members). North Southeast Sulawesi in the “Medium” category.